MHD free convection boundary layer flow on a horizontal circular cylinder in a Williamson hybrid ferrofluid with viscous dissipation - Marjan, Mohd Daud; Muhammad Khairul Anuar, Mohamed; Norhafizah, Md Sarif; Ong, Huei Ruey; Elfiano, Eddy (Semarak Ilmu, 2024)
The present research examined the flow of a horizontal circular cylinder immersed in a Williamson hybrid ferrofluid via free convection boundary layer flow. The fluid flow is modelled by means of governing partial differential equations that incorporate viscous dissipation and magnetohydrodynamic (MHD) effects. Prior to being converted into a more practical partial differential equation, these dimensional equations are reduced to a non-dimensional form by utilising appropriate dimensionless variables. The Keller-box approach is then used to solve these equations with fewer dependent variables numerically. Graphical representations are generated, and the impacts of different interested factors are analysed using MATLAB software. According to the results, the hybrid ferrofluid outperformed ferrofluid with the same particle volume fraction in terms of skin friction and convective heat transfer capabilities.